Islamic distributive justice accounting model to reduce payroll system inequities - Rahman, Karlina Ghazalah; Alimuddin, Alimuddin; Indrijawati, Aini; Sundari, Sri (Edelweiss Applied Science and Technology, 2025)
This study examines how to implement distributive fairness accounting in the payroll system of the foundation organization. It employs qualitative research methods with a phenomenological approach. The phenomenological studies utilized in this research are based on the researcher’s linkage to examine the phenomena experienced by key informants more deeply. The results indicate that the payroll system in the foundation’s organization was not established based on justice but rather due to the capitalist values held by the foundation. Two contributing factors are identified: minimizing costs while maximizing benefits and the familial nature of the organization. Distributive justice accounting presents an alternative for improving the payroll systems of organizations. The fair value applied is based on the Quran, which states that the head of the Education Foundation organization must intend to provide welfare to employees for the sake of Allah SWT. Employees are also expected to apply Islamic work ethics when performing their duties. The findings reveal that the payroll system in the foundation’s organization was not created based on justice but rather due to the capitalist values of the foundation. Distributive justice accounting serves as an alternative for enhancing the payroll systems of organizations. The fair value referenced is based on the Quran, which emphasizes that the head of the Education Foundation organization must aim to provide welfare to employees for the sake of Allah SWT. Employees should also adhere to Islamic work ethics while fulfilling their responsibilities.